Pattern of tobacco consumption and related factors among the people residing in a rural area - Khan, Nirmeen Rifat; Mahmood, Afzalur Rahman (Bangladesh Medical Journal, 2016)
This descriptive cross-sectional study was conducted with an aim to find out the pattern of tobacco consumption and its related factors in a rural area of Sripur upazilla under Gajipur district of Bangladesh. The study was carried out from February 2010 to June 2010. Total sample was 361. Mean age of respondents was 39.01 years with standard deviation of ±13.54 years. Among them 85.04% and 14.96% were male and female respectively. Most (27.16%) of them were illiterate and 26.86% were able to write their name only. Maximum were businessman (25.48%) followed by day laborers (20.23%). Their mean monthly family income was 8,867.31 taka with SD of ± 7733.56 taka and 39.88% of them had monthly family income equal or below 5000 taka. The most frequent types of tobacco use among male was cigarette smoking (77.20%) and among female, consumption of jarda was 81.48%. The mean age of starting tobacco consumption was around 22 years and mean duration of consumption was nearly 17 years. Regarding causes behind tobacco consumption, majority (29.92%) answered 'addiction'. Mean daily expenditure on tobacco consumption was 24 taka. Maximum (90%) were known about harmful effects of tobacco consumption and regarding harmful effects they mentioned 'cancer' in 74.54% cases and 'tuberculosis' in 64.7%. The findings of this study suggest that, tobacco use is more prevalent among the poor, illiterate middle-aged segment of the population. Bangladesh Med J. 2015 Jan; 44 (1): 32-37